(untitled) (Research, Society and Development, 2022)
The research aims to investigate in the scientific literature, the unfolding of phonological awareness in the literacy cycle and its stimulus from the pedagogical practice. A bibliographic research of qualitative and quantitative approaches was used as a method for the construction of knowledge on the proposed theme, as well as aligned with the State of the Art research mode. With the results of the data collection using the google academic and Scielo platforms, it is possible to reflect on the scientific productions regarding the relevance of the development of phonological awareness skills for the progress of a literacy that values reflective learning, having the theoretical framework composed of 49 productions, whose publication period followed the time frame between 2018 and 2022. Evidencing, however, the importance of literacy teacher training. It is noteworthy, however, that the choice of effective methods is essential for the development of reading and writing, as well as the use of playfulness in the learning process in literacy. It can be seen that the stimulus and development of phonological skills is a driving element in literacy.